PENGARUH KUALITAS PRODUK DAN PENETAPAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL TERIOS PADA PT CAPELLA MEDAN DAIHATSU CABANG DURI - Manurung, Gresi Florentina; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This research was conducted at PT. Capella Medan Daihatsu Duri Branch, located on street Duri-Dumai km 3.5 in front of the dsf gate. The purpose of this study was to determine the effect of product quality and pricing on purchasing decisions for terios cars at PT. Capella Medan Daihatsu Branch of Duri. Product quality and pricing (X1X2) meanwhile purchasing decisions (Y). The research method used is quantitative descriptive analysis obtained from the results of a questionnaire measured by a Likert scale which is then processed by the SPSS program. The sample of this study was 85 respondents from the population who were calculated using the Slovin formula. This research uses simple linear regression analysis method and multiple linear regression analysis. The results showed that the quality of the product had an effect on purchasing decisions for terios cars with a value of t co+unt> t table (8,712> 1,663) and significance (0,000 <0.05). Pricing affects the decision to purchase terios cars with a value of t count> t table (11.099> 1.663) and significance (0.000 <0.05). Product quality and pricing on purchasing decisions for terios cars with a value of F count> F table (63.158> 3.11) and significance (0.000 <0.05). It can be concluded that product quality and pricing have a positive and significant effect on purchasing decisions for terios cars at PT. Capella Medan Daihatsu Branch of Duri. Keywords : Product Quality, Pricing, Purchasing Decisions